2011
DOI: 10.1371/journal.pone.0022363
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibitory Effects of CysLT1 Receptor Antagonists on P2Y6 Receptor-Mediated Signaling and Ion Transport in Human Bronchial Epithelia

Abstract: BackgroundCysteinyl leukotriene (CysLT) is one of the proinflammatory mediators released by the bronchi during inflammation. CysLTs exert their biological effects via specific G-protein-coupled receptors. CysLT1 receptor antagonists are available for clinical use for the treatment of asthma. Recently, crosstalk between CysLT1 and P2Y6 receptors has been delineated. P2Y receptors are expressed in apical and/or basolateral membranes of virtually all polarized epithelia to control the transport of fluid and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…2C and D). The replacement of apical normal KH solution by a low Cl - concentration solution generated a favorable serosal to the mucosal Cl - gradient, and the increase in I SC response could be due to Cl - secretion as shown in our previous studies [21,25,27]. To confirm that nobiletin-stimulated I SC responses were due to Cl - secretion, ion substitution experiments were performed.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…2C and D). The replacement of apical normal KH solution by a low Cl - concentration solution generated a favorable serosal to the mucosal Cl - gradient, and the increase in I SC response could be due to Cl - secretion as shown in our previous studies [21,25,27]. To confirm that nobiletin-stimulated I SC responses were due to Cl - secretion, ion substitution experiments were performed.…”
Section: Resultsmentioning
confidence: 76%
“…FRET imaging experiments were performed using the MetaFluor Imaging System with FRET module (Molecular Devices, Downingtown, PA, USA) as described previously [24,25]. In brief, 16HBE14o- cells were transfected with the Epac-based cAMP sensor with Lipofectamine 2000 according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of PDEs by montelukast may be beneficial to ischemic neuronal injury, because the resultant accumulation of cAMP protects neurons from ischemic brain injury (Tsukada et al, 2004;Lin et al, 2009) and inhibitors of PDE3 (cilostazol) and PDE4 (rolipram) have protective effects on neurons (Tanaka et al, 2010;Schaal et al, 2012). In addition, its inhibitory effects on P2Y receptors (Mamedova et al, 2005;Pugliese et al, 2009;Lau et al, 2011) may be protective, because downregulation of the novel P2Y-like receptor GPR17 protects from ischemic neuronal injury after focal cerebral ischemia in rats (Ciana et al, 2006;Zhao et al, 2012). Moreover, montelukast has antioxidative effects in peripheral tissues (Muthuraman and Sood, 2010;Coskun et al, 2011;Mohamadin et al, 2011); in a preliminary study, we also found its moderate CysLT 1 Rindependent antioxidative activity in primary neurons (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both CFTR Cl -channels and cAMP-dependent K + channels expressed in 16HBE14o-cells could by stimulated by cordycepin through the activation of the cAMP/protein kinase A signaling pathway (Bleich and Warth, 2000;Li and Naren, 2010). In addition to the activation of the cAMP-dependent pathway, cordycepin evoked a concentration-dependent increase in intracellular [Ca 2+ ] as measured by Fura-2 imaging (Lau et al, 2011) (Fig. 4).…”
Section: Abmentioning
confidence: 87%